Building settlement measurement system and reporting on LabVIEW-based soil liquefaction simulator - Pratama, Bagas Adha; Zahrah, Dian Fajria; Setiowati, Sulis (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
A one-axis shaking table soil liquefaction simulator is utilized to study soil behaviour and characteristics, enabling efforts to mitigate liquefaction-indicated soil behaviour. Traditionally, the process of measuring and documenting building settlement, which is a soil variable that indicates liquefaction, involves the use of a pen, paper, and measuring instrument. Therefore, build a measurement system consisting of LVDT displacement sensors and NI cRIO-9025 as the main components, along with LabVIEW software as a novel medium to acquire, process, display, and record measurement data to provide increased measurement accuracy equivalent to traditional instruments. The soil used as material in the test was represented by silica sand with a density percentage of 40-70%. By utilizing the measurement system uses a linear regression scaling method with a sampling time implemented during testing with 100 ms or 10 data/second and descriptive statistical analysis, the soil liquefaction simulator achieves precision with an average measurement error of ±0.89 mm and a reporting operational time efficiency rate of 95.80%. Thus, the accuracy rate of the simulator with the method used in the system is 96.31%.